De quelles indignations parle-t-on ? - Leïla Tazir (Cahiers de Civilisation Espagnole Contemporaine)
It has been a complete rotation in my life, tells Javier, 29 years old activist during the 15-M. If this movement transformed individuals' affects into collective actions in 2011, it has also contributed to shaking up the bipartisan political structure since 2014. It has also impacted trajectories and life stories from one part of outraged people (Indignados). This fight has participated in the rise of a social-political pro-democratic imaginary. Examining this question of indignation requires an interdisciplinary approach between the academic disciplines of social history and political anthropology. I led the survey about the 15 M' historical roots, mainly in Cordoba, where its metamorphosis are plural and overlaps trajectories, memories, and spaces outside and inside the institutions.' Often related to the « civilizational crisis, » the 15-M revealed a big issue: the democratic deficit that some collectives try to fill in.